Genetically engineered bacteriophages as novel nanomaterials: applications beyond antimicrobial agents - Kim, Seong-Min; Heo, Hye Ryoung; Kim, Chang Sup; Shin, Hwa Hui (Frontiers in Bioengineering and Biotechnology, 2024)
Bacteriophages, also known as phages, are viruses that replicate in bacteria and archaea. Phages were initially discovered as antimicrobial agents, and they have been used as therapeutic agents for bacterial infection in a process known as "phage therapy." Recently, phages have been investigated as functional nanomaterials in a variety of areas, as they can function not only as therapeutic agents but also as biosensors and tissue regenerative materials. Phages are nontoxic to humans, and they possess selfassembled nanostructures and functional properties. Additionally, phages can be easily genetically modified to display specific peptides or to screen for functional peptides via phage display. Here, we demonstrated the application of phage nanomaterials in the context of tissue engineering, sensing, and probing.Hard to dissolve in water Cho et al. (2020)